SİKLON TİPİ BİR KURUTUCUDA ZENCEFİLİN KURUMA DAVRANIŞININ ARAŞTIRILMASI - TORAMAN, SEDA (Fırat Üniveristesi, 2015)
Bu çalışmada, siklon tipi konvektif bir kurutucuda zencefil dilimlerinin ince tabaka kuruma davranışı araştırılmıştır. Deneyler dört farklı kurutma havası sıcaklığında (40, 50, 60 ve 70 ?C) ve üç farklı kurutma havası hızında (0.8, 1.5 ve 3 m/s) yapılmıştır. Kuruma kinetiğini belirlemek için zencefil dilimlerinin kütle değişimi bütün kurutma havası şartlarında kaydedilmiştir. Kurutma havası sıcaklığı ve hızının zencefil dilimlerinin kuruma hızı, boyutsuz nem oranı, difüzyon katsayısı, aktivasyon enerjisi ve konvektif ısı transfer katsayısı üzerindeki etkileri araştırılmıştır. Nem oranı verileri on iki farklı modele uygulanmış ve bu modellerin performansı korelasyon katsayısı (R), ki-kare (?2) ve tahminin standart hatası (RMSE) ile tespit edilmiştir. Midilli ve Küçük modeli zencefil dilimlerinin ince tabaka kuruma verilerini açıklayan en uygun model olmuştur. Midilli ve Küçük modelinde, R=0.95432, ?2=0.008339581, RMSE=0.090408072 olarak elde edilmiştir. Kuruma işleminin azalan hız periyodunda gerçekleştiği zencefil dilimlerinden havaya olan nem transferi deneysel olarak belirlenen difüzyon katsayısı yardımıyla ifade edilmiştir. Zencefil dilimlerinin difüzyon katsayısı değerleri 2.807x10-10-6.977x10-10 m2/s aralığında değişmiştir. Konvektif ısı transfer katsayısı değerleri ise 0.33-2.11 W/ m2?C aralığında değişim göstermiştir. Anahtar Kelimeler: İnce tabaka kurutma modelleri, difüzyon katsayısı, konvektif ısı transfer katsayısı, zencefil

In this work, the thin layer drying behavior of ginger slices in a cyclone type convective dryer were investigated. Drying experiments were carried out at four different drying temperatures (40, 50, 60 and 70 °C) and three drying air velocity (0.8, 1.5 and 3 m/s). In order to obtain drying data, the changes in the mass of ginger slices were recorded as well as the drying air properties. The effects of drying temperature and air velocity on the drying rate and moisture ratio, diffusion coefficient, activation energy and convective heat transfer coefficient of the ginger slices were investigated. The moisture ratio data were fitted to the twelve mathematical models and performance of these models was determined by correlation coefficient (R), reduced chi-square (?2) and root mean square error (RMSE). For the thin layer drying of ginger slices, the Midilli and Kucuk model was the best descriptive model. From the Midilli and Kucuk model for ginger slices, it was determined that R=0.95432, ?2=0.008339581, RMSE=0.090408072. The moisture transfer from the ginger slices occurring during the falling rate period of drying was characterized by determining experimentally the diffusion coefficient into the air. The diffusion coefficient values of ginger slices were changed in the range of 2.807x10-10-6.977x10-10 m2/s. The average convective heat transfer coefficient values of ginger slices were varied in the range of 0.33-2.11 W/ m2?C. Key words: Thin layer drying models, diffusion coefficient, convective heat transfer, ginger
Investigation of the drying behavior of ginger in cyclone type dryer
Keywords: Makine Mühendisliği